In vitro comparative quality evaluation of different brands of Amlodipine Tablets Commercially available in Jimma Town, South-western Ethiopia. - Abera Milkesa; Gemmechu Hasen; Tesfaye Mohammed; Yesuneh Tefera Mekasha; Duresa Dedefo; Belachew Umeta; Sultan Suleman (PLoS ONE)
Background The incidence of hypertension in persons 25 years of age and older is estimated to be 46% in Africa, where it is still very common. This concerning rate could be explained by the pharmaceutical markets' accessibility to poor quality antihypertensive drugs. Thus, the purpose of this study was to evaluate and compare the quality different brands of Amlodipine Tablets Commercially available in Jimma Town, South-western Ethiopia. Methods The quality control test was conducted from August 30, 2019 to February 27, 2020 at Jimma University in the Laboratory of Drug Quality Control (JuLaDQ). The laboratory test was carried out in accordance with WHO inspection guidelines and United States Pharmacopeia. A statistically significant was considered when P<0.05. For further comparison of the in-vitro dissolution profiles of amlodipine tablets, model-independent model-dependent parameters and statistical Dunnetts tests for ensuring bioequivalence were used to further compare the in-vitro dissolution profiles. Results With the exception of brand AMD-5 (1/10), the remaining nine (n = 9) brands were within WHO visual inspection criteria. The quality control parameters such as friability, weight variation, identity, assay, and dissolution test were within the United States Pharmacopeia. The model independent parameters (f1, and f2) confirmed that, all generic products were bio-equivalence, and interchangeable with comparator product. The model dependent approaches revealed the Weibull model (AMD-10), the Zero order (AMD-3), and the Korsemeyer-Peppas models were the most effective predictions for the release of the pharmaceutical substance from the dosage form. The Korsemeyer-Peppas model (r2 ≥0.9695) was the best descriptive model for determining the amlodipine drug kinetics from the point of view of all brands examined. The evaluated amlodipine brand tablets were in line with quality standards. The model independent methods confirmed that the generic brand tablets were interchangeable in clinical practice. The tested products follow more than two drug release kinetics. Conclusion The study revealed a manifest discrepancy in the dissolution profiles' releases. Therefore, it is strongly advised to use appropriately designed dissolution profile evaluation methods with various pH values in the dissolution media, as well as to do comprehensive visual inspections. This will make it easier to do a thorough investigation of any potential quality issues that might be related to various generic products available in the pharmaceutical market.